Peace and Conflict Impact Assessment of the Presidential Amnesty Programme for Niger Delta Ex-Militants - Jarikre, Mathias; Wilson, Nsikanabasi; Orebiyi, Taiwo Philip; Osogolo, Francis (NIU Journal of Humanities, 2026)
Fifteen years after granting presidential amnesty to ex-militants as part of the strategic approach to peacebuilding in Nigeria’s Niger Delta, it is imperative to conduct a Peace and Conflict Impact Assessment (PCIA) of the Presidential Amnesty Programme (PAP). A plethora of studies on the PAP are limited to a vague and undefined broad set of conclusions. This article provides a reflection of the PAP using PCIA framework in peacebuilding. The objective is to advance the minimalist and maximalist approaches to peacebuilding in the context of negative and positive peace in the Niger Delta region. A mixed research method utilizing descriptive survey and semi-structured interviews was adopted. The findings reflect an interesting complex intersection of issues inextricably linked to negative and positive peace. The article argued that the PAP overwhelming mandate to stabilize the region for increased crude oil production using negative peace to safeguard critical national assets without prioritizing the needs of ex-militants and communities could engender the broader drivers of armed insurrection. It concludes that PAP reintegration process has been reduced to Nigeria’s albatross and a prisoner of its own creation as a result of the brinkmanship and identity politics where few ex-militant commanders and PAP officials appropriate a common heritage as an ethnic estate. Considering the challenges of economic reintegration and obtaining formal jobs, the article suggests that one strategic way to exit the PAP is to establish an Oil and Gas Assets Surveillance and Protection Corps (OGASPC) to absolve ex-militants in formal employment for effective surveillance and protection at the community level. Keywords: Peace and Conflict Impact Assessment, Amnesty, ex-militants, Niger Delta, Minimalist, Maximalist.